3 Implantable loop recorders in adult congenital heart disease: a single-centre experience. (28th April 2017) - Tabassum, Rahim; Okeke, Zita; Arif, Sayqa; Clift, Paul; Bowater, Sarah; Thorne, Sara; Marshall, Howard; Bono, Joseph de; Hudsmith, Lucy
Abstract : Introduction: Evaluation of rhythm disease can be difficult in patients with adult congenital heart disease (ACHD), especially if symptoms are infrequent or atypical, further compounded by the presence of electrocardiogram abnormalities. Implantable loop recorders (ILRs) are useful in evaluating these disorders and correlating ECG abnormalities with patient symptoms. We therefore sought to evaluate the use of ILRs in our ACHD population. Methods: A single-centre retrospective case note review of all our ACHD patients who had insertion of an ILR. Results: 119 patients (median age [37 years 29 – 48], 54 male) received an ILR, 60 complex (eg. Fontan, Ebstein, rTOF, Senning, Mustard) and 59 simple. Indications included syncope 52 (44%), pre-syncope 15 (13%), palpitations 36 (30%), prior to consideration of PFO closure 4 (3%) and other 4 (3%) and unknown 8 (7%). It took a median of 97 (52 – 200) days before a decision was made about whether symptoms correlated with a rhythm disorder or not. Outcomes include 18 (15%) significant conduction disease requiring a pacemaker, 21 (17%) patients had evidence of a new tachyarrhythmia on interrogation of the ILR, with 4 (3%) receiving an implantable cardiac defibrillator. In 41 (34%) patients the ILR was able to confirm that symptoms correlated with normal heart rhythm. Conclusions: ILRs provided a useful tool to investigate ACHD patients with symptoms suggestive of heart rhythm disorders. Identifying these patients led to timely potentially life-saving therapy.